Konstruksi Sosial Komunitas Pesantren mengenai Isu Radikalisme (Studi Kasus Pada Pesantren Salaf & Modern di Kota Malang) - Tsabita Shabrina Alfanani (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Radicalism became a phenomenon widely discussed in inter-religious life. In practice, Islam and pesantren is often associated with acts of terrorism and other violence since the action was perceived as an extension of religious radicalism with jihad and amar ma’ruf nahi mungkar as basic commands. The focus of this study is to analyze how komunitas pesantren (pesantren community) perception about radicalism and how the process of those perceptions is formed. This research was conducted in two komunitas pesantren with different characteristic in Malang City : Alhayatul Islamiyah as salaf (traditional) pesantren and Ma’had Al-Qalam as modern pesantren. By using a qualitative approach and case study, this study resulted in three broad conclusions. First, salaf pesantren community’s perception regarding the issue of radicalism tends to moderate and tolerant. Meanwhile, the perception of modern pesantren community on the issue of radicalism tends to vary; Second. The Construction process could be explained by the dialectical process from Berger & Luckman’s social construction theory consisting of three simultaneous processes: externalization, objectivation and internalization. In the process, the researcher found three types of komunitas pesantren in perceiving radicalism which is contextual moderate and tolerant (as the majority group); fundamental (idealist) and pragmatic. At the salaf pesantren, Kyai was an important figure in constructing value, while at modern pesantren the background, social settings and media give more influence in the construction process about radicalism; Third, the pattern similarity at salaf pesantren motivated by cultural hegemony by constructing value on a single base culturally affiliated to the nahdliyin tradition, while varying perceptions of modern pesantren arise from it’s heterogeneous base. However, both of pesantren does not encourage their santri to act radically.Keywords: Social Construction, Pesantren Community, Radicalism